Within-Host Competition Drives Selection for the Capsule Virulence Determinant of Streptococcus pneumoniae - Lysenko, Elena S. (Cell Press, 2010)
For many opportunistic pathogens, it is unclear why their virulence determinants and expression of pathogenic behavior have evolved when damage or death of their host offers no obvious selective advantage to microbial growth or survival [1–3]. Many pathogens initiate interactions with their host on mucosal surfaces and must compete with other members of the microflora for the same niche. Here we explore whether competitive interactions between microbes promote the acquisition of virulence characteristics. During model murine nasal colonization, Haemophilus influenzae outcompetes another member of the local flora, Streptococcus pneumoniae, by recruiting neutrophils and stimulating the killing of complement-opsonized pneumococci [4]. For S. pneumoniae, resistance to opsonophagocytic killing is determined by its polysaccharide capsule [5, 6]. Although there are many capsule types among different S. pneumoniae isolates that allow for efficient colonization, virulent pneumococci express capsules that confer resistance to opsonophagocytic clearance. Modeling of interspecies interaction predicts that these more virulent S. pneumoniae will prevail during competition with H. influenzae, even if production of a capsule is otherwise costly. Experimental colonization studies confirmed the increased survival of the more virulent S. pneumoniae type during competition. Our findings demonstrate that competition between microbes during their commensal state may underlie selection for characteristics that allow invasive disease.